The potential of Inventori Laporan Masalah Pendengaran (ILAMP) to be used as a hearing screening tool among Malaysian - Amir, Najihah; Rahmat, Sarah; Lamri, Marina L. Alisaputri @ Marina (IIUM Press, 2022)
ABSTRACT Self-reported hearing loss questions can be used as an alternative hearing screening tool when other standard hearing tests (e.g. Pure Tone Audiometry) are unavailable. However, a comprehensive self-reported hearing loss survey is not available in Malay. This study aimed to develop a Malay self-reported hearing loss inventory for adults known as Inventori Laporan Masalah Pendengaran (ILaMP) and investigate its potential to be used as a screening tool. This study has obtained the approval of the IIUM Research Ethics Committee (IREC). It is a cross-sectional study. The stages involved in this study are; 1) The development of a preliminary version of ILaMP, 2) content validation involving six experts, 3) face validation and pre-testing involving 15 laypeople, and 4) pilot testing involving 71 adults aged ≥19 years from Kuantan. In the pilot study, the subjects need to undergo a complete hearing test and fill in the ILaMP. Result: A total of 58 questions with 10 domains were developed. Good content validity for ILaMP was established with an average content validity index for scale (S-CVI) of 0.995 and content validity index for item (I-CVI) ranging between 0.83 to 1.00. Face validity results showed that 100% of the subjects agreed that ILaMP is suitable for a self-reported hearing survey. Pre-testing showed that the majority of the subjects agreed that the items were readable (100%), suitable to be asked (99.5%), the sentence was clear (98.6%), and had good sentence structure (99.1%). The initial analysis from the pilot study showed a significant difference in the total score of ILaMP between normal and hearing loss subjects (p: 0.021). ILaMP has shown good content & face validity, good pre-testing results and could differentiate between normal-hearing and hearing-impaired populations. It has good potential to be used as an alternative hearing screening tool due to its performance, easy administration, and cost- and time- efficiency. However, further investigation on the sensitivity, specificity, and accuracy of ILaMP needs to be conducted on a larger population. Keywords: hearing screening, hearing loss, self-report, self-report survey Acknowledgement: We would like to thank Global Precision Sales and Services Sdn Bhd for assisting in data collection.